Business Model Innovation Paths and Tools - Marikka Heikkilä; Harry Bouwman; Jukka Heikkilä; Timber Haaker; Carolina Lopez Nicolas; Angelika Riedl (Slovenia, 2025)
There is a multitude of tools available for Business Model Innovation (BMI). However, Business models (BM) and supporting tools are not yet widely known by micro, small and medium sized companies (SMEs). In this paper, we build on analysis of 61 cases to present typical BMI paths of European SMEs. Firstly, we constructed two paths for established companies that we named as 'I want to grow' and 'I want to make my business profitable'. We also found one path for start-ups: 'I want to start a new business'. Secondly, we suggest appropriate BM toolsets for the three paths. The identified paths and related tools contribute to BMI research and practise with an aim to boost BMI in SMEs.
Proceedings of the 29th Bled eConference "Digital Economy"